The Condition of Special Library Services for People with Disability in "Children with Disability Foundation" (YPAC) Surabaya - Mutia, Fitri (Record and Library Journal, 2015)
The Research about library services for people with disabilities is still found rarely, therefore, in this Â research Â case, Â the Â researcher Â try Â to Â discuss Â the Â title Â in Â order Â to Â enrich Â the Â librarianship scientific. This research uses a quantitative approach with the descriptive type. Some findings of the Â data Â presented Â in Â this research case Â is Â about Â the Â collection, Â type Â of Â service, Â the Â library manager and Â the Â library Â space of Surabayaâs YPAC. Â In Surabayaâs YPAC is available Â only Â in hard copy collections amounted to approximately 1000-1500 ex, that dominated the collection of fiction Â (stories/illustrated Â fables). Â The Â condition Â of Â most Â of Â the Â collection Â is Â very Â alarming because it was never noticed, classified specifically and many collections are laid out horizontally as Â high Â book Â shelf Â height Â exceeds Â available. Â YPAC Â library Â runs Â only Â circulation Â services manually, and organized by Â teachers Â who Â graduate from educational of Â school Â for Â disabled (SLB). Regarding Â the Â library Â are Â in Â good Â condition Â and Â clean, Â there Â are Â 4 Â and Â 3 Â units Â of Â rack collection of tables and chairs, but the air circulation is not good because the ventilation system only comes from a window so that the temperature inside the room pretty hot.